Infiltration of Whiteman Ego in The Cultural Ethos of The African People: A Textual Analysis of Dele Charley’s Drama The Blood of A Stranger - Samuel Idowu, Adewumi, (IJRDO - Journal of Social Science and Humanities Research, 2017)
Africans, before the era of colonialism had been living a well structured pattern of life which guided their daily existence. The partitioning of Africa at the Berlin conference of 1884/85 upturned the traditional patterned life system of the Africans thus, giving way to the dictates of the white masters who then hold the aces. This paper, therefore, takes a foray into the exploitative antics of the white lords at changing directly or indirectly the socio-cultural ethos of the Africans, as vividly portrayed in the text. Things were no longer the same for the Africans with the takeover of government from the Africans by the minority whites.